Consistent effects of biodiversity loss on multifunctionality across contrasting ecosystems - Fanin, Nicolas (2019)
Understanding how loss of biodiversity affects ecosystem functioning, and thus the delivery of ecosystem goods and services, has become increasingly necessary in a changing world. Considerable recent attention has focused on predicting how biodiversity loss simultaneously impacts multiple ecosystem functions (that is, ecosystem multifunctionality), but the ways in which these effects vary across ecosystems remain unclear. Here, we report the results of two 19-year plant diversity manipulation experiments, each established across a strong environmental gradient. Although the effects of plant and associated fungal diversity loss on individual functions frequently differed among ecosystems, the consequences of biodiversity loss for multifunctionality were relatively invariant. However, the context-dependency of biodiversity effects also worked in opposing directions for different individual functions, meaning that similar multifunctionality values across contrasting ecosystems could potentially mask important differences in the effects of biodiversity on functioning among ecosystems. Our findings highlight that an understanding of the relative contribution of species or functional groups to individual ecosystem functions among contrasting ecosystems and their interactions (that is, complementarity versus competition) is critical for guiding management efforts aimed at maintaining ecosystem multifunctionality and the delivery of multiple ecosystem services.